Case study - Burnet, Graeme Macrae, 1967- (Biblioasis, 2022)
"The Booker-shortlisted author of His Bloody Project blurs the lines between patient and therapist, fiction and documentation, and reality and dark imagination. London, 1965. An unworldly young woman believes that a charismatic psychotherapist, Collins Braithwaite, has driven her sister to suicide. Intent on confirming her suspicions, she assumes a false identity and presents herself to him as a client, recording her experiences in a series of notebooks. But she soon finds herself drawn into a world in which she can no longer be certain of anything. Even her own character. In Case Study, Graeme Macrae Burnet presents these notebooks interspersed with his own biographical research into Collins Braithwaite. The result is a dazzling--and often wickedly humorous--meditation on the nature of sanity, identity and truth itself, by one of the most inventive novelists writing today."--